PERBANDINGAN APLIKASI PUPUK HAYATI VP3 PADA BERBAGAI KOMBINASI TERHADAP PRODUKSI KACANG HIJAU (Vigna radiata L.) DILAPANG - firman hidayat (AGRONISMA, 2020)
The aims of this study was to determine the effect of applying VP3 organic fertilizer with compost and vermiwash on the production of green bean plants and to determine the effect of applying VP3 organic fertilizer with compost and vermiwash compared to the combined organic fertilizer. with compost and NPK fertilizer in the production of green bean plants. planted in the field. This investigation was carried out on dry land located in the residential area of Bumi Asri, Dau district, Malang. In addition to the Basic Laboratory, Faculty of Agriculture, Malang Islamic University, from June to August 2019. The research design used was a simple randomized complete design (RBD) consisting of 8 treatments and was repeated 3 times. The study results showed that the treatment of the biological fertilizer VP3 combined with 75% NPK tended to provide the highest average yield in the production of mung bean crops, but not significantly different from the treatment of the biological fertilizer VP3 combined with 75% and 100% vermiwash.